Assessing Urban Water Management Sustainability of a Megacity: Case Study of Seoul, South Korea - Kim, Hyowon; Son, Jaewoo; Lee, Seockheon; Koop, Stef; van Leeuwen, Kees; Choi, Young June; Park, Jeryang (MDPI, 2018)
Many cities are facing various water-related challenges caused by rapid urbanization and climate change. Moreover, a megacity may pose a greater risk due to its scale and complexity for coping with impending challenges. Infrastructure and governance also differ by the level of development of a city which indicates that the analysis of Integrated Water Resources Management (IWRM) and water governance are site-specific. We examined the status of IWRM of Seoul by using the City Blueprint (R) Approach which consists of three different frameworks: (1) Trends and Pressures Framework (TPF), (2) City Blueprint Framework (CBF) and (3) the water Governance Capacity Framework (GCF). The TPF summarizes the main social, environmental and financial pressures that may impede water management. The CBF assesses IWRM of the urban water cycle. Finally, the GCF identifies key barriers and opportunities to develop governance capacity. The results indicate that nutrient recovery from wastewater, stormwater separation, and operation cost recovery of water and sanitation services are priority areas for Seoul. Furthermore, the local sense of urgency, behavioral internalization, consumer willingness to pay, and financial continuation are identified as barriers limiting Seoul's governance capacity. We also examined and compared the results with other mega-cities, to learn from their experiences and plans to cope with the challenges in large cities.
Keywords: CITY BLUEPRINT APPROACH; CLIMATE-CHANGE; RESOURCES MANAGEMENT; AIR-TEMPERATURE; CITIES; RESILIENCE; PRECIPITATION; CHALLENGES; GOVERNANCE; FRAMEWORK